CA 125 concentration in portal blood as a predictor of resectability in pancreatic tumor - Szwedziak, Krzysztof; Szymański, Dariusz; Strzelczyk, Janusz (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study: Pancreatic cancer is one of the most frequent cancers in the world. Only 20% of patients seem to have disease confined to the pancreas, but in only every second case the tumor turns out to be resectable during surgery. Tumor markers may be a useful tool in differentiating benign from malignant pancreatic tumors and in clinical staging. The purpose of the study is to assess CA 125 utility as a predictor of resectability in pancreatic tumor. Material and methods: 66 patients were operated on for pancreatic tumor between October 2010 and July 2012. CA 125 concentration was measured in peripheral and portal blood. 57 patients were diagnosed with malignant and 9 with inflammatory tumor. Seven patients had metastases to the liver. Radical surgery was performed in 34 patients. Results : Significantly higher CA 125 concentration in portal blood was found in the pancreatic cancer than in the inflammatory tumor group (36.5 ±99.6 vs. 16.4 ±26.5; p < 0.05). CA 125 concentration in peripheral blood and in portal blood as well of patients with malignant pancreatic tumors and with metastases to the liver was significantly higher than in the group without metastases (146.15 ±256.1 vs. 18.5 ±17.5; p < 0.01 and 147.5 ±261.2 vs. 19.7 ±24.3; p < 0.05, respectively). CA 125 values in the group without metastases to the liver and in the case of radical surgery were significantly higher in portal than in peripheral blood (19.7 ±24.3 vs. 18.5 ±17.5; p < 0.001 and 13.2 ±15.0 vs. 13.0 ±15.2; p < 0.001, respectively). Conclusions : Determination of CA 125 concentration in peripheral blood and in portal blood as well might be a useful tool in differentiating between malignant and inflammatory pancreatic tumors and when decisions on surgery extensiveness are being made.